Surat-Surat Kerajaan untuk Penguasa Kerinci: Tinjauan Terhadap Naskah Cod.Or. 12.326 Koleksi Perpustakaan Universitas Leiden - Hafiful Hadi Sunliensyar (Jumantara: Jurnal Manuskrip Nusantara, 2019)
Not  all of Jawi manuscripts in the Kerinci had documented and transliterated by Voorhoeve. For example, the document Cod. Or. 12. 326, the collection of Universiteit Leiden Library or the document ML 396, the collection of Perpustakaan Nasional. This research purpose is for knowing the contain of the text  of ML 396/Cod. Or. 12.326 and considering the historical background ofthe text. The method that utilized in this research is collecting of data, transliterating and interpretating text of manuscripts from historical perspective. The result of this research, known that three manuscripts are surat piagam (royal charter) from Jambi Sultanate to Depati Suta Menggala in Tanah Seleman, Kerinci. Meanwhile, two manuscripts other are surat titah (royal commandment letter) for Depati Empat. The first surat titah from Sultan Ahmad Syah and Pangeran Suta Mangunjaya, contains the adjuration of troop assistance to attact Palembang people. The second surat titah from Sultan Ahmad Syah, contains the bidding of Sultan in order to Depati Empat still recognized his authority and cooperated with him, accompanied by special rewards that offered. The five manuscripts was issued in ongoing conflict between two successors of Jambi Kingdom in 17th century.